Puerperal complications in elective versus emergency caesarean deliveries - Joshi, Ashka; Modi, Maulesh; Shah, Ami; Singh, Kanupriya; Doshi, Haresh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The aim of current study was to compare puerperal complications in elective vs emergency caesarean section. Though similar complications occur in elective and emergency caesarean sections, this study aims to find out which complications are more common in either of them. Methods: A prospective case comparative study was conducted at GCS Medical College and Hospital, Department of Obstetrics and Gynecology, Ahmedabad from 01 December 2020 to 01 June 2021. Results: The emergency caesarean section (CS) rates (36) were more common in the age group of 21-25 years than the elective CS (32). Emergency CS was most common in primipara women (69). The most common risk factor is previous known history of hypothyroidism and most common indication is known history of previous lower segment caesarean section (LSCS). 10 patients in elective CS and 8 patients in emergency CS had previous LSCS. Body mass index (BMI) of 26 patients in elective CS was ranging between 24.9-29.9 kg/m2 when compared to 28 patients with similar BMI in emergency CS. Overweight patients underwent more emergency CS when compared to elective CS. Most common intra-operative complication was adhesions between rectus sheath and muscle and second most common was dense adhesion. Most common post op complication was breast engorgement and mastitis. Conclusions: There is a significant difference between the number of patients in elective and emergency CS group when common indications are seen (p<0.05). Similarly, statistically significant is observed between the 2 groups when post-operative complications are observed (p<0.05).